An improved coupling model for the lithosphere‐atmosphere‐ionosphere system. Issue 4 (24th April 2014) - Kuo, C. L.; Lee, L. C.; Huba, J. D.
Abstract In our previous model for the lithosphere‐atmosphere‐ionosphere coupling, the background magnetic field was assumed to be perpendicular to the horizontal plane. In the present paper, we improve the calculation of currents in the atmosphere by solving the current density J directly from the current continuity equation ∇ J = 0. The currents in the atmosphere can be solved for any arbitrary angle of magnetic field, i.e., any magnetic latitude. In addition, a large ratio (~10) of Hall to Pedersen conductivities is used to generate a large Hall electric field. The effects of atmospheric currents and electric fields on the ionosphere with lithosphere current source located at magnetic latitudes of 7.5°, 15°, 22.5°, and 30° are obtained. For upward (downward) atmospheric currents flowing into the ionosphere, the simulation results show that the westward (eastward) electric fields dominate. At magnetic latitude of 7.5° or 15°, the upward (downward) current causes the increase (decrease) of total electron content (TEC) near the source region, while the upward (downward) current causes the decrease (increase) of TEC at magnetic latitude of 22.5°or 30°. The dynamo current density required to generate the same amount of TEC variation in the improved model is found to be smaller by a factor of 30 as compared to that obtained in our earlier paper. We also calculate the ionosphere dynamics with imposed zonal westward and eastward electric field based on SAMI3 code. It is found that the eastward (westward) electric field may trigger one (two) plasma bubble(s) in the nighttime ionosphere.